Teaching Factory Based on Scientific Creativity to Enhance Students' Soft Skills and Sustainable Entrepreneurship - Samsuri, Taufik; Habibi, Habibi; Ikhsan, Muhamad (International Journal of Essential Competencies in Education, 2024)
This study aimed to assess the validity and effectiveness of a Teaching Factory (TEFA) model based on scientific creativity in enhancing students’ soft skills and fostering sustainable entrepreneurship. The TEFA approach was validated through expert evaluations and tested through two production processes involving 15 university students. The research focused on improving soft skills such as communication, teamwork, creativity, leadership, and time management, alongside sustainable entrepreneurship skills like opportunity identification, resource utilization, and entrepreneurial action. Data were collected using observation sheets and analyzed through descriptive statistics and ANOVA to compare students' performance across the two production processes. The results showed significant improvements in students' soft skills and sustainable entrepreneurship, with the TEFA approach based on scientific creativity proving highly effective. Average soft skill scores increased from "Poor" to "Good" after the intervention, and similar improvements were observed in sustainable entrepreneurship scores. The structured pedagogical cycle employed—encompassing need identification, curriculum development, implementation, evaluation, and reflection—successfully bridged the gap between theoretical knowledge and practical application in entrepreneurship education. However, a limitation of the study was its small sample size, indicating the need for further research with larger and more diverse populations. These findings suggest that the TEFA approach based on scientific creativity can be a valuable addition to university entrepreneurship programs, better preparing students for the challenges of the global business landscape.